Dynamics of Adaptive Immune Cell and NK Cell Subsets in Patients With Ankylosing Spondylitis After IL-17A Inhibition by Secukinumab - Jiang, Yutong; Yang, Mingcan; Zhang, Yanli; Huang, Yefei; Wu, Jialing; Xie, Ya; Wei, Qiujing; Liao, Zetao; Gu, Jieruo (Frontiers in Pharmacology, 2021)
Background: Anti-IL-17A therapy is generally effectively applied in patients with Ankylosing Spondylitis (AS) to achieve and maintain remission. However, the influence of anti-IL-17A on the composition of the immune system is not apparent. Our prospective study was to explore the changes in immune imbalance regarding T cell, B cell and natural killer (NK) cell subsets after secukinumab treatment in AS patients. Methods: Immune cell distribution of 43 AS patients treated with secukinumab for 12 weeks and 47 healthy controls (HC) were evaluated. Flow cytometry using monoclonal antibodies against 25 surface markers was accomplished to explore the frequencies of lineage subsets. The differences between HC, AS pre-treatment, and post-treatment were compared using the paired Wilcoxon test, Mann-Whitney U test, and ANOVA. Results: AS patients had altered immune cell distribution regarding T cell and B cell subsets. Apart from activated differentiation of CD4+ T cell, CD8+ T cell and B cell, higher levels of cytotoxic T (Tc) two cells and Tc17 cells were noted in AS patients. We confirmed that helper T (Th) one cell became decreased; however, Th17 cells and T follicular helper (Tfh) 17 cells went increased in AS. After 12 weeks of secukinumab therapy, CRP and ASDAS became significantly decreased, and meanwhile, the proportions of Th1 cells, Tfh17 cells and classic switched B cells were changed towards those of HC. A decreased CRP was positively correlated with a decrease in the frequency of naïve CD8+ T cells (p = 0.039) and B cells (p = 0.007) after secukinumab treatment. An elevated level of T cells at baseline was detected in patients who had a good response to secukinumab (p = 0.005). Conclusion: Our study confirmed that AS patients had significant multiple immune cell dysregulation. Anti-IL-17A therapy (Secukinumab) could reverse partial immune cell imbalance.